Photothermal/Photodynamic Therapy with Immune‐Adjuvant Liposomal Complexes for Effective Gastric Cancer Therapy. (10th April 2019) - Meng, Xiangbo; Wang, Ke; Lv, Lin; Zhao, Ye; Sun, Chen; Ma, Lianjun; Zhang, Bin
Abstract: A diagnosis and therapeutic strategy for gastric cancer is developed herein by combining thermosensitive liposomal (TSL)‐based photothermal/photodynamics therapy (PTT/PDT) with chemotherapy and adjuvant immunotherapy. IR820, a photothermal agent, paclitaxel (PTX), an antitumor drug, and imiquimod (R837), a Toll‐like‐receptor‐7 agonist, are coencapsulated into a TSL drug delivery system. These formed PTX‐R837‐IR820@TSL complexes exhibit excellent optical properties, good dispersibility, and stability. Under NIR light irradiation, the measurement of singlet oxygen production and thermal efficiency indicate promising potential of PTX‐R837‐IR820@TSL complexes for PTT and PDT. Confocal microscopy and small animal NIR imaging demonstrate tumor targeting ability of the liposomal complexes to gastric cancer cells. In vitro cell viability assays and in vivo animal experiments show prominent antitumor efficiency of PTX‐R837‐IR820@TSL complexes upon NIR light irradiation. This excellent therapeutic efficacy is attributed to the simultaneous chemotherapy and PTT/PDT. Furthermore, the liposomal complexes under NIR irradiation would ablate tumors to generate a pool of tumor‐associated antigens, which is able to promote strong antitumor immune responses in the presence of those R837‐containing liposomal complexes acted as adjuvant. These results indicate that the multifunctional liposomal complexes could realize a remarkable synergistic therapeutic outcome in gastric carcinoma. Abstract : A multifunctional liposomal drug delivery system for gastric carcinoma diagnosis and therapy by combining IR820‐based PTT/PDT, chemotherapy, and immunotherapy is presented in this study. The obtained results demonstrate that PTX‐R837‐IR820@TSL complexes with a diameter of about 100 nm under NIR light irradiation can realize a remarkable synergistic therapeutic outcome in gastric carcinoma.